Food price trends in South Korea through time series analysis. (December 2018) - Kim, T.H.; Park, Y.; Myung, J.; Han, E.
Abstract: Objectives: This study analyzed the relative time trends of prices of healthy versus unhealthy foods in South Korea for the 20 years from 1995 to 2015. Study design: Time series analysis was used. Methods: We analyzed price trends of selected food items in the food groups of grains, vegetables, meats, sweets, spices, fast foods, and non-alcoholic beverages. We obtained nominal prices from the monthly reports of the 2006 Consumer Price Survey for representative items in each food group. Results: The real price of processed meat increased by 1.2 percentage points less than the overall Consumer Price Index (CPI) increase, whereas beef prices increased by 2.4 percentage points more than the CPI increase. The price of soda was cheaper than that of other non-alcoholic beverages, whereas the real prices of milk showed statistically significantly larger yearly increases (by 1.4 percentage points, respectively) than that of the CPI. The yearly increases in the real prices of pizza, hamburgers, and fried chicken—three representative fast-food items that were mostly consumed by eating out or through home delivery—were statistically significantly less than those of the CPI (by 1.5, 1.4, and 0.3 percentage points, respectively). Conclusions: Our results show that relatively healthy foods showed higher real price increases than the CPI increase, whereas the opposite occurred for unhealthy foods. Highlights: We analyzed the relative time trends of prices of selected foods in South Korea. Time series analysis was used for the 20 years from 1995 to 2015. Relatively healthy foods showed higher real price increases than the Consumer Price Index increase.